The Use of Number Ruler Teaching Aids to Improve Students' Mathematics Learning Outcomes - Laelatul Arofah (Jurnal Pendidikan Profesi Guru, 2023)
The activity of learning mathematics in class V MI Ma’arif NU 01 Karangmangu on the prescycle showed that the learning process is still not effective, the process of learning is still guided by the teacher, so that the students seem passive and only listen to the material given by the teachers. Students are still under the KKM. With that circumstance, the teacher decided to make improvements in learning through class action research. The purpose of research action of this class is to improve the learning results of students of class V MI Ma'arif NU 01 Karangmangu on the material of operations counting round numbers using a tool for guarding the number. Student activity adds, student participation is only 27% with an average grade of 50,8, and active students are only 18%, there is an increase in Cycle I with a result of 64%, class average of 70,9 active students 73 % at the end of Cycle II academic excellence score of 91 % with a grade average of 80,9 and student activity of 100%. From the learning results that have been improved, it can be concluded that the use of machine tools can improve the learning outcomes and activity of students of grade V MI Ma'arif NU 01 Karangmangu, with the results all in accordance with what is expected.